Pengaruh Loyalitas Dan Mutasi Kerja Terhadap Kinerja Karyawan Pada Petshop Dunia Satwa Kabupaten Kediri - Sela Rully Amita Sari; Edwin Agus Buniarto; Iing Sri Hardiningrum (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This research uses independent variables, namely loyalty and job transfers, as well as the dependent variable, namely employee performance. The sample in this research were employees of the Kediri Regency animal world pet shop. Data was obtained through questionnaires, observations and interviews. The sampling technique was carried out using a simple random sampling technique using the Slovin formula. The analysis techniques used are validity test, reliability test, normality test, linearity test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, hypothesis t test and F test, and coefficient of determination (R2) test using the SPSS version 25 program. The results of this research show that the loyalty variable has a partial effect on employee performance. It is known from the results of the loyalty t test that the value of sig. = 0.000 > 0.05 and the job transfer variable has a partial effect on employee performance, this is known from the results of the t test, the sig value. = 0.002 > 0.05. Meanwhile, the results of research on loyalty and job transfers simultaneously influence employee performance, this is known from the F test, sig value. = 0.000 < 0.005